2018
DOI: 10.1177/2165143417750093
|View full text |Cite
|
Sign up to set email alerts
|

Predicting College Completion Among Students With Learning Disabilities

Abstract: The authors analyzed National Longitudinal Transition Study-2 (NLTS2) data to examine the role of high school academic preparation and receipt of postsecondary academic support services (PASS) in predicting college completion among students with learning disabilities. Logistic regression analyses revealed that students who earned a 3.0 GPA in a college prep curriculum were more than twice as likely to complete college than those with a similar GPA who did not complete a college prep curriculum. Furthermore, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
15
2
Order By: Relevance
“…These findings are inconsistent with those of Yu et al (2018), who had not found a significant relationship between support receipt and postsecondary completion. However, their analyses did find that college students who had completed a college prep curriculum in high school and had received college supports were almost 7 times more likely to graduate than were students who had not received supports.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…These findings are inconsistent with those of Yu et al (2018), who had not found a significant relationship between support receipt and postsecondary completion. However, their analyses did find that college students who had completed a college prep curriculum in high school and had received college supports were almost 7 times more likely to graduate than were students who had not received supports.…”
Section: Discussioncontrasting
confidence: 98%
“…Given (a) the importance of completing college, (b) the low rate of college completion for students with LD, (c) research suggesting that supports benefit college outcomes for students with disabilities, and (d) the impact of support use varying by disability type, it is imperative to understand the link between support use and achieving positive postsecondary outcomes for students who comprise the largest proportion of students with disabilities, those with LD (Raue & Lewis, 2011). Moreover, the recent findings by Yu et al (2018) regarding predictors of college completion represented by 150 students with LD in the NLTS2 sample contradicts prior findings in the literature regarding the role of accessing academic supports. As noted by Joshi and Bouck (2017) in their examination of high school factors that impact postsecondary access for students with LD, “researchers need to assess the supports required by students with learning disabilities to systematically prepare them to not only attend but also complete the postsecondary education of their choice” (p. 11).…”
Section: Characteristics Affecting Retention and Graduationcontrasting
confidence: 66%
See 1 more Smart Citation
“…We selected possible confounders related to both group assignment and the outcome (Sex, Age, Cohort, Highest preeducation, Days between application and enrollment), and to increase the power to test the effect, 26 we added measures that were outcome proxies (Grades in Secondary Education 27 and Parallel programs). We imputed missing data using the MICE package 28 and VIM package.…”
Section: Data Selection and Imputationmentioning
confidence: 99%
“…An interesting finding of this analysis was that mean high school matriculation grades were found significant in predicting college GPA for both participants with and without LD. Because the Israeli matriculation mean grades reflect the knowledge the student has acquired during high school, a support program throughout the high school years can equip both the LD and NLD students with the tools they need to succeed in college (Yu, Novak, Lavery, Vostal, & Matuga, 2018). Personnel who work with high school and transition-age students with disabilities must be made aware of the importance of providing the information and skills students need to ensure that they disclose their disability and seek disability-specific support when they go to college.…”
Section: Discussionmentioning
confidence: 99%